Vascularized Fibula TMJ Reconstruction: A Report of Five Cases featuring Computerized Patient-specific Surgical Planning. Issue 8 (18th August 2022) - Powers, David B.; Breeze, John; Erdmann, Detlev
Abstract : Background: Mandibular defects involving the condyle represent a complex reconstructive challenge for restoring proper function of the temporomandibular joint because it requires precise bone graft alignment, or alloplastic materials, for complete restoration of joint function. The use of computerized patient-specific surgical planning (CPSSP) technology can aid in the anatomic reconstruction of mandibular condyle defects with a vascularized free fibula flap without the need for additional adjuncts. The purpose of this study was to analyze clinical and functional outcomes after reconstruction of mandibular condyle defects using only a free fibula graft with the assistance of virtual surgery techniques. Methods: A retrospective review was performed to identify all patients who underwent mandibular reconstruction utilizing CPSSP with only a free fibula flap without any temporomandibular joint adjuncts after a hemimandibulectomy with total condylectomy. Results: From 2018 to 2021, five patients underwent reconstruction of mandibular defects involving the condyle with CPSSP technology and preservation of the native temporomandibular articulating disk. The average age was 62 years (range, 44–73 years). The average follow-up period was 29.2 months (range, 9–46 months). Flap survival was 100% (N = 5). The maximal interincisal opening range for all patients was 22–45 mm with no lateral deviation or subjective joint pain. No patients experienced progressive joint hypomobility or condylar migration. Conclusion: The use of CPSSP technology can aid in the anatomic reconstruction of mandibular condyle defects with a vascularized free fibula flap through precise planning and intraoperative manipulation with optimal functional outcomes.